Kajian Aspek Bentuk Lahan dan Geologi Berdasarkan Mikrotremor Dalam Perencanaan Ruang Kawasan Rawan Gempa di Kabupaten Bantul Daerah Istimewa Yogyakarta (Studi Kasus: Kecamatan Bantul, Jetis, Imogiri, dan Kretek) - Gunawan, Arif; Khadiyanto, Parfi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The high risk of loss due to frequent occurrence of earthquakes increasingly demanded adaptable spatial planning based on disaster mitigation. This study examines the geologic and earth science aspect in earthquake prone area of Bantul Regency. Analysis was presented in microtemor map and microtemor parametric distribution table per unit of land, land use comparison of pre and post 2006 earthquake, and implementation assessment of land use planning in the study area. Inferential analysis by linear regression indicated the correlation of vulnerability index to collapse ratio. The study found diversity in geologic sediment characteristics and local landform in respons to earthquake altering the seismic vulnerability index thus affecting collapse ratio. Therefore there is a need for a detailed spatial plan whichinclude a detailed geological sediment and local landform analysis.